Reformulating Corporate Criminal Liability for Environmental Damage through Restoration-Oriented Sanctions and Compliance Mechanisms in Indonesia Framework - Aryani, Fajar Dian; Mufty, Abdul Malik (Kosmik Hukum, 2026)
Environmental degradation in Indonesia is increasingly driven by corporate activities, yet corporate criminal liability remains ineffective in delivering deterrence and ecological recovery. This reflects a structural gap between the normative objectives of environmental protection and enforcement outcomes, primarily due to fragmented liability standards and the dominance of fine-centered sanctions. This study aims to reformulate corporate criminal liability by integrating restoration-oriented sanctions and corporate compliance mechanisms into a coherent framework. Using normative doctrinal legal research, this study analyzes statutory regulations, legal principles, and comparative practices to identify structural deficiencies and construct prescriptive arguments. The findings reveal that the existing framework produces largely symbolic enforcement, characterized by limited attribution of corporate responsibility and the absence of mandatory restoration obligations. Financial penalties alone fail to deter misconduct or remedy environmental harm. This study argues that restoration-oriented sanctions reorient criminal punishment toward ecological recovery, while compliance mechanisms embed preventive accountability within corporate governance. The originality lies in advancing an integrated liability model that positions restoration and compliance as core elements of corporate criminal responsibility, contributing to an outcome-oriented approach to environmental criminal law and offering concrete directions for strengthening environmental governance in Indonesia.